The world today current global issues in conjunction with 50th Independence Day - Azman Ab Rahman; Hisham Muhammad Taky Eldin; Hishomudin Ahmad (Center of General Studies, USIM, 2007)
The publication of the 3rd book by the General Studies Centre is based on global issues is light of the celebration of the 50th Independence Day of Malaysia. This book is a collection of various works from writers of various fields and expertise unveiling current global issues. Varieties of writings on the executions, challenges and success faced and achieved is the aspects of politics, economics and social. The issues that are presented also involved language, Islamic law and legislature, communication and media, technology and various other interesting issues relevant to general studies in Malaysia.